Serum calcium levels in rheumatoid arthritis. Issue 6 (December 1981) - Scott, D L; Farr, M; Hawkins, C F; Wilkinson, R; Bold, A M
Abstract : Total and corrected (for albumin) serum calcium levels were investigated in a cross-sectional study of 394 patients with rheumatoid arthritis, 4490 healthy subjects, and 2609 inpatients at a district general hospital. Patients with rheumatoid arthritis had lower mean clacium levels than the healthy subject (p less than 0.001), but had similar levels to inpatients at the district general hospital. Thirty-eight inpatients with rheumatoid arthritis at a hospital for rheumatic diseases had lower mean corrected and total calcium levels than all other groups (p less than 0.01). Corrected or total calcium levels higher than 2.60 mmol/l or corrected calcium levels lower than 2.20 mmol/l were uncommon in the patients with rheumatoid arthritis. A longitudinal study of serum calcium levels in 17 patients with rheumatoid arthritis over 6-48 months showed considerable temporal variation in total and corrected calcium levels. Transient hypercalcaemia and hypocalcaemia occurred occasionally, but for most of the time calcium levels were normal. Changes in calcium levels were not related to changes in clinical, haematological, or immunological parameters of disease activity. Mean serum calcium levels are lower in disease than health; this occurs in RA as well as other diseases.